Collection and Preparation of Shariah Courts' Statistical Data: Studies in Pahang and Penang: (Pengumpulan dan Penyediaan Data Statistik Mahkamah Syariah: Kajian di Pahang dan Pulau Pinang) (Kanun: Jurnal Undang-undang Malaysia, 2016)
Collection and maintenance of statistical data or information is important in any organization that deals with the public, especially courts of law. The data can be used for policy decisions and action plans to improve services or strategic planning. Syariah courts in Malaysia similarly collect statistical data regarding cases registered and disposed of in their respective courts for the above purpose. Accuracy and reliability of such data is imperative so that the policies and action plans designed will solve particular problems or achieve the required objectives. The main objective of this article is to test the accuracy of statistical data collected by the Syariah courts in Malaysia by using the Syariah courts of Pahang and Penang as samples. The methodology used in this article is data collection, with the primary data obtained from court files and interviews with officials. This article aims to identify issues and problems faced by the Syariah courts in Malaysia in the collection and maintenance of statistical data regarding court cases, and to relate these to the effectiveness of the court in administering and disposing of cases. From the data analysed, it was found that the data produced by the court is somehow questionable although not entirely unreliable where there is a difference of 17.1 percent between the data presented by the courts and their own records. The article proposes some improvements in the conclusion.Keywords: statistical data of cases, Syariah courts, records, court management